Peningkatan Kesehatan Gigi Dan Mulut Dengan Cara Kontrol Plak Yang Benar Pada Anak SDN 53 Kota Banda Aceh - Mardiah, Ainun; Reca, Reca; Nuraskin, Cut Aja; Salfiyadi, Teuku; Rahayu, Eka Sri; Munira, Munira (Poltekkes Kemenkes Aceh, 2024)
Plaque control is very important for maintaining oral healt. The habit of maintaining healthy teeth and mouth is influenced by the knowledge one has and proper tooth brushing techniques are very important in achieving dental and oral hygiene. Therefore, delivering dental and oral health education to students is very important. This community service aims to increase knowledge about how to control plaque and how to brush teeth properly and correctly in children at SDN 53 Banda Aceh City. This community service was carried out using a descriptive method, with the target being all 30 class V students at SDN 53 Banda Aceh City. The intervention provided is in the form of education about children's dental health and demonstrations on how to see plaque and how to control plaque (brushing teeth properly and correctly). Keywords: Imroved dental health, plaque control